Oil injection lubrication analysis of a silent chain drive system. (October 2022) - Yang, Jinxing; Feng, Zengming; Wang, Xiaoguang
Highlights: A high-fidelity dynamic model of a silent chain drive system was established that can simulate the real contact between parts. The stability of the established chain drive system model was verified by analysis based on a recursive algorithm. Based on the MPS method, the oil injection lubrication mechanism of the silent chain drive system was studied through co-simulation. A method to study oil lubrication for chain drive systems was proposed. Abstract: Previous investigations on oil lubrication have mainly focused on gear transmission systems. There has been little research on injection lubrication of silent chain drive systems. In this study, a high-fidelity 3D model of a silent chain drive system is established, and the stability of the model is verified through simulation analysis. Using the moving particle semi-implicit (MPS) method, the flow field distribution of the silent chain drive system under the coupling of multiple fields is obtained through co-simulation with RecurDyn and Particleworks. The effects of key parameters, including sprocket speed, injection quantity, lubricant viscosity, and injection angles, on the lubrication performance of the silent chain drive system are investigated. These results provide a reference for future practical application and theoretical research of oil injection lubrication for chain drive systems.